2008
DOI: 10.1158/1078-0432.ccr-07-1606
|View full text |Cite
|
Sign up to set email alerts
|

Gefitinib Radiosensitizes Non–Small Cell Lung Cancer Cells by Suppressing Cellular DNA Repair Capacity

Abstract: Purpose: Overexpression of the epidermal growth factor receptor (EGFR) promotes unregulated growth, inhibits apoptosis, and likely contributes to clinical radiation resistance of non^small cell lung cancer (NSCLC). Molecular blockade of EGFR signaling is an attractive therapeutic strategy for enhancing the cytotoxic effects of radiotherapy that is currently under investigation in preclinical and clinical studies. In the present study, we have investigated the mechanism by which gefitinib, a selective EGFR tyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 28 publications
3
83
0
2
Order By: Relevance
“…Preclinical studies showed that EGFR TKI, such as gefitinib and erlotinib, have radiosensitizing effects at multiple levels including cell cycle arrest, apoptosis, accelerated repopulation and DNA damage repair (50). However, in previous clinical studies, incorporation of TKI in the combined chemoradiotherapy for locally advanced NSCLC was not associated with improved treatment outcomes (51); possible explanations include the cell cycle specific antagonism when combined with concurrent chemotherapy and the unselected patients in these trials.…”
Section: Management Of Local Advanced Nsclc With Tki and Radiotherapymentioning
confidence: 99%
“…Preclinical studies showed that EGFR TKI, such as gefitinib and erlotinib, have radiosensitizing effects at multiple levels including cell cycle arrest, apoptosis, accelerated repopulation and DNA damage repair (50). However, in previous clinical studies, incorporation of TKI in the combined chemoradiotherapy for locally advanced NSCLC was not associated with improved treatment outcomes (51); possible explanations include the cell cycle specific antagonism when combined with concurrent chemotherapy and the unselected patients in these trials.…”
Section: Management Of Local Advanced Nsclc With Tki and Radiotherapymentioning
confidence: 99%
“…It is well known that radioresistance is associated with DNA damage repair, apoptosis and cell cycle checkpoints (31)(32)(33). IR is able to induce DNA damage and apoptosis via reactive oxygen species generated by radiolytic hydrolysis (34).…”
Section: A B Cmentioning
confidence: 99%
“…There are different opinions about whether tyrosine kinase inhibitors that target nuclear kinase activity of EGFR have an effect on the redistribution of DNA-PK. Gefitinib (a tyrosine kinase inhibitor) was observed to suppress nuclear DNA-PK levels in head and neck squamous cell carcinoma cells [13], but not in nonsmall cell lung carcinoma (NSCLC) cell lines A549 [14]. In NSCLC cell lines, unlike wild-type (WT) EGFR, receptors with common oncogenic TKD mutations, L858R or ∆E746-E750, are more sensitive to ionizing radiation and are defective in radiation induced translocation to the nucleus; receptors with these mutations fail to bind the catalytic and regulatory subunits of the DNA-PK.…”
Section: Egfr and The Nhej Mechanismmentioning
confidence: 99%
“…Because Nbs1 functions in a protein complex MRN, an abnormal abundance of Nbs1 may sequester other repair proteins away from the sites of DSBs. Nbs1 is a substrate for the ATM kinase; Nbs1 phosphorylation is a possible connection between EGFR>ERK>ATM>Nbs1, and should be examined in further studies [14].…”
Section: Egfr and The Hr Mechanismmentioning
confidence: 99%